USING PODCAST IN TEACHING SPEAKING AT UNIVERSITAS HAMZANWADI - Muhammad Ali; Laila Wati; M. Adib Nazri; Yulia Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian English as a Foreign Language (EFL) students persistently struggle with speaking proficiency, a challenge exacerbated by teacher-centered instruction that lacks authentic communicative practice. This study aims to investigate the effect of paired podcast activities—unscripted, collaborative digital audio tasks—on students' speaking proficiency. Employing a quasi-experimental pretest-posttest design, the research involved 46 second-semester students at Universitas Hamzanwadi, assigned to an experimental group (n=29) and a control group (n=17). Data were collected through speaking performance tests evaluated via an analytic rubric (assessing pronunciation, fluency, vocabulary, grammar, and comprehension) and a post-intervention student questionnaire. Wilcoxon Signed-Rank tests revealed significant within-group improvements for both cohorts. While the Mann-Whitney U test indicated no statistically significant difference in post-test scores between the groups (p = 0.378), the experimental group demonstrated a descriptively higher mean gain (2.55 vs. 1.24), predominantly in fluency and vocabulary, alongside a homogenized proficiency variance. Furthermore, a medium practical effect size (Cohen's d = 0.551) and highly positive affective responses (Overall M = 3.65) were recorded. The study concludes that despite sample size constraints limiting statistical superiority, paired podcast activities provide a practically meaningful, highly engaging pedagogical framework that accelerates conversational fluency and facilitates peer scaffolding in EFL classrooms.